The inherently distributive aspects of many bargaining interactions - Gifford, Donald G. (Henry Stewart Talks, 2011)
Value claiming and value creation, Problem-solving or integrative bargaining, Distributive or "zero-sum" bargaining contexts, Reservation point, Goals and aspirations, Competitive tactics, Cooperative tactics, Objective criteria, Style contrasted with tactics or strategy, Informational bargaining, Nonverbal cues, Bargaining power, BATNA, Preparation, Home turf, Initial proposals, Anchoring, Responses to initial proposals, Concessions, Threats, Promises, Arguments, Limiting concessions, Consecutive concessions, Closure, Deadlines and ultimatums, Splitting the difference